"If we work as a team, there are success stories." Unpacking team members' perceptions and experiences of what impacts team performance in a maternal and neonatal quality improvement programme in South Africa, before, and during COVID-19. - Willem Odendaal; Ameena Goga; Mark Tomlinson; Yages Singh; Helen Schneider; Solange Mianda; Shuaib Kauchali; Carol Marshall; Terusha Chetty; Xanthe Hunt (PLOS Global Public Health)
Many maternal and neonatal deaths and stillbirths can be avoided if quality of care is improved. The South African National Department of Health implemented a multi-partner quality improvement (QI) programme between 2018 and 2022, in 21 facilities, with the aim to reduce maternal and perinatal mortality. We conducted a qualitative evaluation to explore QI team members' perceptions of the factors shaping variation in team performance. The evaluation was conducted in 15 purposively selected facilities. We interviewed 47 team members from the 14 facilities consenting to participate in the evaluation, over three time points. We conducted 21 individual interviews and 18 group interviews. Data were thematically analysed using ATLAS.ti 8. Based on a preliminary assessment, six teams were rated as well-performing and eight, less well-performing. Patterns of divergence between well-performing and less well-performing teams were then examined through in-depth analysis of the full data set. Well-performing teams had a core team of members with a good understanding of the programme aims and QI methodology; a second in-charge member to ensure leader continuity; and leader stability throughout the implementation period. Well-performing teams were recruited from existing facility service teams who had a positive prevailing work culture. Team leaders' enthusiasm for QI and their ability to mobilise member buy-in, and how well teams worked together, further affected teams' performance. Existing facility contexts, how teams are set up, leadership-and member buy-in into the methodology, affect QI teams' performance. Focusing on these as well as supporting leaders to foster a shared vision and culture of excellence; mitigating contextual and implementation barriers; and strengthening team members' technical QI skills, has the potential to improve QI teams' performance.